THE ROLE OF BOOKS BY PRESIDENTS IN CREATING A NEW SOCIETY (ISLAM KARIMOV AND SHAVKAT MIRZIYOYEV) - Teshaboyeva Nafisa Zubaydulla qizi,; Narzullayeva Farangiz Farrux qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: The literary works of Uzbekistan’s first President, Islam Karimov, and the current President, Shavkat Mirziyoyev, have had a profound and transformative impact on the political, social, and cultural development of the nation. Islam Karimov’s books, including “Uzbekistan on the Path of Independence” and “Independence – Our Greatest Value”, laid the foundational ideological framework for the establishment of the  modern  Uzbek  state.  His  writings  emphasize  the  importance  of  national sovereignty, social stability, unity, and the preservation of Uzbek identity, highlighting historical experiences, cultural heritage, and moral principles as key pillars for state-building. Karimov’s intellectual contributions were instrumental in fostering a sense of patriotism, civic responsibility, and national consciousness among citizens, especially during the formative years of independence after 1991.